Modeling photovoltaic grid inter-shading - Chitkusheva-Dimitrovska, Biljana; Cepin, Marko; Golubovski, Roman; Spasevska, Hristina (National Library of Serbia, 2020)
Photovoltaic energy conversion is an efficient renewable source affordable as a technology even on the household level. Several technological aspects are subject to continuous improvement. This paper tackles the possibilities for denser panel population of a photovoltaic plant thus more efficient space utilization. The objective is to develop a mathematical model of inter-shading among the photovoltaic panels. The model calculates the electrical energy obtained from panels and considers the shading among the panels. The geographical location of the plant location, the distances between the solar panels and their angle of inclination, the dimensions of the panels and the time interval under evaluation are the parameters which are important for placing the power plant. The results show how much electric energy can be obtained from a certain set of photovoltaic panels. The results indicate, what are the distances between the panels for better allocation of resources when deciding on the number of solar panels and their arrangement.